Surgical, clinical and pathological comparison on the used of omental pedicle and bone marrow stroma cell therapy following sciatic nerve neurotmesis in rabbit model - Al-Timmemi, Hameed Ali (2011)
In Europe and U.S.A. approximately 300,000 peripheral nerve injuries occur each year. Common causes of peripheral nerve injuries are direct mechanical trauma (transection, crush injury, traction, or avulsion), compression, thermal injury, and neurotoxins. Management of peripheral nerve injury (PNI) requires an understanding of the Anatomy, Pathology, Pathophysiology and surgical principles. However, the rate of success of functional recovery from PNI is far from satisfactory in spite of advances in microsurgery. The poor functional recovery has been attributed to factors intrinsic to the motor or sensory cell body and to elements at the site of injury including nerve gaps, scar tissue formation and inadequate time frame required for both supportive growth factors and extracellular matrix molecules to be effective for nerve regeneration. Thus in this study a comprehensive investigation was directed toward developing procedures to improve nerve regeneration focusing on biological approaches to promote nerve healing through: i) the role of omental pedicle in nerve regeneration and functional recovery. ii) Isolation and identification of the mesenchymal stem cells from bone marrow, which currently is the target of studies on tissue and organ regeneration in view of their plasticity for nerve regeneration and functional recovery. This study was conducted with the hypothesis that omental pedicle transposition (OMPT) and bone marrow stromal cells (BMSCs) implantation promote sciatic nerve regeneration and functional recovery. Hence the objective of the study was to investigate the effects of omental pedicle transposition and bone marrow mesenchymal stem cells implantation on the sciatic nerve following neurotmesis in a rabbit model. Towards this end, the investigation compares the efficacy of omental pedicle transpositioning and mesenchymal stem cells implantation on transected sciatic nerve. Evaluation of nerve regeneration brought about by each treatment was based on clinical, neurohistological, ultrastructural, histomorphometric examinations evaluation and relative gastrocnemius muscle weight gain.Sixty healthy rabbits were used in the study. The animals were divided into three equal groups (n=20) and subjected to coaptation of transected sciatic nerve with epineural sutures (ENS) which served as control and omental pedicle transposition (OMPT) and bone marrow stromal cells (BMSCs) implantation comprising the treated groups. Evaluation on the regeneration and functional recovery of the transected sciatic nerve based on the above approaches were performed on days 14, 28, 56 and 112 post operations (PO). Clinical and gross pathological examinations showed complete healing of the skin incision of the operated limb with evidences of mild adhesion between the coaptated sciatic nerve and the surrounding tissues in the BMSCs implanted group while there was no evidence of adhesion in the OMPT group. Clinical motor signs of the operated limb and walking in the OMPT and BMSCs implanted groups showed earlier recovery compared to the control group on day 55 PO. Clinical signs were supported by the earlier registration of muscle contractions force in both groups while regain of muscle mass ensued earlier in the OMPT group. Sensory clinical signs indicated the progress of sensation on day 112 PO in both the OMPT and BMSCs implanted groups. Histopathological findings of the proximal segment of the sciatic nerve in the OMPT and BMSCs implanted groups indicated early regeneration demonstrated by parallel arrangement of nerve fibers, increased angiogenesis, increased concentration of Schwann cells and minimal scar tissue formation on day 28 PO.Semi-thin sections of the proximal and distal segments of the transected nerve showed normal arrangement and distribution of nerve fibers and normal epineurium development. The dorsal root ganglia and spinal cord contained neurons with Nissl bodies indicating nerve recovery of the OMPT and BMSCs groups. Histopathological findings of the gastrocnemius muscle in the OMPT and BMSCs groups showed progressive regeneration. These histopathological finding of nerve tissue regeneration supported the clinical signs in the operated limb. Regeneration of nerve fibers was further strengthen by ultrastrutural finding of the sciatic nerve which showed well-developed myelination, activated Schwann cells, well-developed basement membrane and endoneurium which confirmed the histological and pathophysiological regeneration of the transected sciatic nerve in the OMPT and BMSCs groups. Histomorphometric analysis showed an increase in the number of myelinated nerve fibers, increased diameter of myelinated nerve fiber and increased thickness of myelin sheath and axon diameter in the OMPT and BMSCs groups, indicating sound reinnervation of the transected nerve. However, regenerative changes in the OMPT group occurred slightly earlier compared to the BMSCs group. This could indicate that omental pedicle transposition has a slight advantage over stromal cell implant in terms of transected nerve therapy. Gastrocnemius muscle mass weight gain progressed to normal in the OMPT and BMSC groups indicated the reinnervation of the gastrocnemius muscle. The findings of this study provided ample evidences that surgical application of omental pedicle transposition and bone marrow stem cells implantation on injured peripheral nerve could promote early regeneration and functional recovery of the transected nerve. Thus, there is tremendous potential in the application of OMPT and BMSCs implantation in the treatment of peripheral nerve injuries.